ANALISIS CIPP DALAM KOMPETENSI GURU BK DI LOMBOK TENGAH - Aulia, Fitri; Widiana, Wayan; Ratnaya, Gede (Universitas Hamzanwadi, 2023)
The competence of BK teachers is divided into four competencies, namely pedagogic, personality, social and professional. This competence must be fulfilled considering the mandate of the Law in the Republic of Indonesia's education minister no. 27 of 2008. This study seeks to evaluate the competence of counseling teachers with the CIPP evaluation theory. The research method uses CIPP evaluation research, namely Context, Input, Process, and Product. The research was conducted at SMPN 6 Kopang, Central Lombok. Based on the results of the research conducted, it was found that the competence of counseling teachers was still not effective. The obstacles found were (1) weak commitment and responsibility, (2) weak mastery of technology, (3) weak collaboration skills, (4) minimal access to self-development.